PLANNING INCOME OF STATE FUNDING AIMED AT THE DEVELOPMENT OF EDUCATIONAL AND RESEARCH ACTIVITIES OF THE UNIVERSITY - S. Vikulov (Вестник университета)
The processes of budgetary financing of the educational and research activities of the university are considered. The methodology of planning the income of financial resources within the state financing programs with the aim of timely distribution of these resources within the university and maximization of their expenditure is proposed. The author pays special attention to taking into account possible changes in the amount of funding that can occur within the framework of the state financing program during the year. Conclusions on the need for a correct and timely distribution of financial resources are drawn.